2019
DOI: 10.1021/acs.chemmater.8b03818
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Coexisting n-Type Electronic and Oxide Ion Conductivities in Donor-Doped Ba–In-Based Oxides under Oxidizing Conditions: Roles of Oxygen Disorder and Electronic Structure

Abstract: Surface oxygen reduction reaction (ORR) rates at n-type oxide-based mixed ionic–electronic conducting (MIEC) solid oxide fuel cell (SOFC) cathodes can be expected to be enhanced relative to that at p-type MIEC cathodes due to the greater availability of electrons at higher energies in the band structure needed for the charge transfer reaction. However, given the difficulty of achieving coexisting oxygen vacancies and electrons in the conduction band under oxidizing cathode conditions, no stable n-type MIEC cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Since interstitial oxygen defects quasi-interstitial sites can be expected to be with much higher concentrations than cation vacancies as reported for other donor doped perovskites oxides [39] Fig. 5b shows the O1s spectra of x = 0, 0.05 and 0.1 samples.…”
Section: Synergistic Effects Of Sb Doping On Oxygen Vacancy Formation...mentioning
confidence: 67%
See 1 more Smart Citation
“…Since interstitial oxygen defects quasi-interstitial sites can be expected to be with much higher concentrations than cation vacancies as reported for other donor doped perovskites oxides [39] Fig. 5b shows the O1s spectra of x = 0, 0.05 and 0.1 samples.…”
Section: Synergistic Effects Of Sb Doping On Oxygen Vacancy Formation...mentioning
confidence: 67%
“…High electronic conductivity found in BSFSb as reported in many doped Fe-rich perovskites, percolation paths have been proposed for electrons movement through the crystal comprised exclusively of Fe−O−Fe bonds and the excess charge by oxygen vacancy due to dopants. As reported that in Fe rich perovskites [39,40,[44][45][46] , the 3deg orbital of Fe cations may overlap with the 2pσ orbitals of O 2− ions to form σ-bonds, and the 3dt2g orbital of Fe ions may overlap with the 2pπ of O 2− ions to form π-bonds e.g. eg−pσ−eg and t2g−pπ−t2g bonds.…”
Section: Synergistic Effects Of Sb Doping On Oxygen Vacancy Formation...mentioning
confidence: 99%
“…Because Ba 2 Sc 2 O 5 has a brownmillerite-type structure, which has energetically stabilized ordered oxygen vacancies, achieving a fully hydrated phase is difficult. However, once Ba 2 Sc 2 O 5 is hydrated and the oxygen vacancies are consumed, a perovskite-type structure will be obtained. , In fact, perovskite-type BaScO 2 (OH) was reported only by Cervera et al in the form of nanosized powder synthesized by a low-temperature technique . However, a method for the synthesis of a dense pellet of hydrated perovskite-type Ba–Sc oxides has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] Additionally, L-SDC should transform from an oxide-ion conductor to n-type MIEC, which conducts oxide-ions as well as electrons. 38,39 Therefore, it can be inferred that the n-type MIEC formed in situ causes a drastic increase in the oxygen permeation flux at high applied voltages. We previously reported that the formation of an SDC interlayer with an isotropic oxide-ion conduction pathway enhanced the oxygen incorporation into c-LSBO from the triple phase boundary (TPB), 32) as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%